2011
DOI: 10.4102/aveh.v70i1.89
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between central corneal thickness and corneal curvature in adult Nigerians

Abstract: Purpose: The aim of this study was to provide average values for central corneal thickness (CCT) and corneal curvature (CC) and also to determine a regression model for the relationship between CCT and CC in adult Nigerians without glaucoma.Methods: A total of 95 subjects consisting of 56 males and 39 females aged between 20 and 69 years with mean age of 47.1 ± 14.1 years were recruited for the study. Central corneal thickness was measured by ultrasound pachymetry (SW-1000P ultrasound pachymeter, Tianjin Suowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 12 publications
2
11
0
Order By: Relevance
“…7 The average corneal curvature and power of young undergraduates students with high myopia in our study was significantly different (P=0.0001) from the normal average value recorded for emmetropes from previous studies, which was about 7.85mm that is in myopes the corneal curvature was found to be relatively decreased. 1,12,13 We found in our study that female students with high myopia had shorter mean average corneal curvature, similar to Li et al, but females without refractive errors had slightly higher mean average corneal curvature than males in another study. 13,14 A result similar to a study done by Iyamu and Osuobeni were they found that age and gender did not affect corneal curvature in emmetropes, however we only found a significant effect with gender on the corneal curvature of the young undergraduates with high myopia.…”
Section: Discussionsupporting
confidence: 90%
“…7 The average corneal curvature and power of young undergraduates students with high myopia in our study was significantly different (P=0.0001) from the normal average value recorded for emmetropes from previous studies, which was about 7.85mm that is in myopes the corneal curvature was found to be relatively decreased. 1,12,13 We found in our study that female students with high myopia had shorter mean average corneal curvature, similar to Li et al, but females without refractive errors had slightly higher mean average corneal curvature than males in another study. 13,14 A result similar to a study done by Iyamu and Osuobeni were they found that age and gender did not affect corneal curvature in emmetropes, however we only found a significant effect with gender on the corneal curvature of the young undergraduates with high myopia.…”
Section: Discussionsupporting
confidence: 90%
“…Significant alterations in CCT may interfere with accurate measurement of intraocular pressure (IOP), and underestimation of IOP due to corneal thinning has the potential to delay diagnosis and treatment of glaucoma. Corneal thickness provides valuable information about possible changes in the cornea due to disease, trauma, or hypoxia [ 27 ]. Therefore, evaluation of corneal thickness is essential in a wide range of ocular disorders such as glaucoma, keratoconus, corneal refractive surgery, dry eye, and atopic keratoconjunctivitis [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 shows the various studies that have investigated and reported on CCT measurements in normal African subpopulations. 31,32,35,54,55,56,57,58,59,60,61,62 Half of the studies (n = 6) have been undertaken in West-Africa (Nigeria). The instrument used to measure CCT is an important consideration when mean CCT measurements are compared across different studies.…”
Section: African Studies On Central Corneal Thicknessmentioning
confidence: 99%